Accessibility mapping using mobile application for wheelchair user / Ahmad Amirul Aqil Roslan and Muhammad Azamuddin Mohamad Asrul - Roslan, Ahmad Amirul Aqil; Mohamad Asrul, Muhammad Azamuddin (Universiti Teknologi MARA (UiTM), 2024)
One the disabilities named by the Department of Social Welfare Malaysia is physical impairment. Wheelchair user can be one of them. Wheelchair user always faces with the problem of being below the normal line of sight of the drivers, pedestrians, and other road users. It can be exposed them to danger if others cannot see the wheelchair user quickly enough. This blind spot has caused accidents involving wheelchairs on roads and sidewalks. Therefore, this project focuses on the development of accessibility mapping using the mobile application for wheelchair users around the Universiti Teknologi MARA (UiTM) Seri Iskandar campus area.